Atrophie blanche complicated with lower limb infection and maggot growth: A case report - Zhou, Bo; Qin, Haotian; Huang, Yicong; Wang, Quanzhen; Zhang, Jian; Xiao, Yingfeng; Peng, Yanbin; Yu, Fei (Frontiers in Surgery, 2022)
BACKGROUND Atrophie Blanche(AB) is rare in clinic which affects 1% to 5% of the population. It mainly occurs in middle-aged female adults, with an average age of 45. However, there are rare cases of children infected with the disease. And it is a thrombotic vascular disease, which also known as ivedo vasculitis or segmental hyaline vasculitis, which characterized by chronic recurrent painful ulcers of lower leg (especially the foot and ankle). Its recovery can leave ivory-white atrophy spots, accompanied by pigmentation and telangiectasia. Its common complication is parasitic growth of microorganisms infected with soft tissue ischemic necrosis in lower limbs. Infection combined with microbial parasitism is one of the surgical infection, it is rare to have a large number of maggot microbial parasitism. which may be amputated or even life-threatening. Understanding the complications, early and timely surgical debridement, and wound repair are particularly important. With the help of relevant cases, it is of great significance to summarize the relevant knowledge and treatment methods of the disease and formulate subsequent clinical guidance. CASE SUMMARY A 59-year-old female patient, was hospitalized because of “repeated ulceration of skin of right lower leg for three years, aggravation and maggot growth for three days.” In last three years, right calf skin soft tissue ischemia infection necrosis. “Atrophie Blanche(AB)” was diagnosed in dermatology department two years ago. After hormone treatment, her right leg improved. One year ago, there was another ischemic infection and necrosis of skin and soft tissue of right leg. The patient did get treated at a hospital but applied “Musk” on her wound. When tendon and some bones of the wound were exposed, where accompanied by a large number of maggots, microorganisms grew and crawled from the wound for three days before they came to our department for treatment.